847 Inflammasome activation in M2 macrophage restrain the immune suppressive function. (9th November 2020) - Zhang, Ronghua; Wang, Tienan; Lin, Qing
Abstract : Background: Macrophage is an important component in tumor microenvironment (TME) and plays multiple roles in tumor initiation, progression and metastases. In response to various stimuli within TME, macrophage exhibits high level of functional heterogeneity. There are two distinct groups of macrophages: M1 macrophage exhibits pro-inflammatory phenotype with high levels of TNF-a, IL-6, and IL-1ß, while M2 macrophage displays immune suppressive phenotype with high levels of anti-inflammatory cytokines such as IL-10 and TGF-ß. In response to the M2 cytokines, myeloid cells within the TME further acquire higher expression of PD-L1 and thus inactivate T cells. M2 cytokines can also directly inhibit T cell activation. As a result, re-polarizing M2 macrophages becomes a key concept for cancer immunotherapy. The NLRP3 inflammasome is acquired by macrophages to fight against endogenous danger signals. Macrophage NLRP3 activation has been observed in several tumor models, but the function of NLRP3 on macrophage polarity remains controversial. Inflammasome activation with IL-1ß/IL-18 secretion was reported to promote M1 polarization. However, NLRP3 activation was also reported to promote M2 polarity through up-regulation of IL4 in asthma model Methods: Here, we have established an in vitro human macrophage NLRP3 activation system (figure 1), coupled with M2 macrophage polarization assay, to dissect the role of NLRP3 in macrophage phenotype. Results: Our results indicate that NLRP3 activation restrained M2 phenotype and further enhanced T cell activation in an M2/T cell co-culture system (figure 2). Conclusions: Inflammasome could be the potential target for cancer by modulating T cell activation through macrophage polarization regulation